Phytochemicals, Antioxidant and Anticancer Properties of Camellia japonica L. Mistletoe Extracts: Phytochemicals, Antioxidant and Anticancer Properties of Camellia Mistletoe - Min Young Kim; Ji Hye Kim (Journal of Tropical Life Science, 2022)
The present study aims to investigate the phytochemical profiles, in vitro antioxidant and antiproliferative properties of methanol and 70% ethanol extracts of Camellia mistletoe. Both extracts were analyzed for contents of total flavonoid, total carotenoid and L-ascorbic acid, and antioxidant properties such as scavenging capacities (1,1-diphenyl-2-picrylhydrazyl, O2- and NOÂž), ferrous ion chelating and reducing power. MTT assay was used to assess the antiproliferative properties against human cancer cell lines. The results showed that the methanol extracts of Camellia mistletoe contained higher total flavonoids (16237 mg rutin equivalents/100 g) and carotenoids (49175 mg/100g) with higher DPPH (IC50 = 0.6 mg/mL), superoxide (IC50 = 0.6 mg/mL), nitric oxide (IC50 = 0.5 mg/mL) radical scavenging and reducing power (IC50 = 1.1 mg/mL) activities than those of ethanol extracts (p < 0.05). In addition, methanol extracts showed much higher antiproliferative activity against A375 (IC50 = 118.1 Î¼g/mL) and HCT116 (IC50 = 148.4 Î¼g/mL) cells than ethanol extracts whereas higher inhibitory effects of MCF7 (IC50 = 139.9 Î¼g/mL), Hela (IC50 = 127.1 Î¼g/mL) and HepG2 (IC50 = 84.2 Î¼g/mL) cell proliferation in the ethanol extracts of Camellia mistletoe. The data from this study suggest that Camellia mistletoe is a potential source of phytochemical compounds with antioxidant and antiproliferative properties.